Koenraad Brosens, Leen Kelchtermans, Katlijne Van der Stighelen (eds.), Family Ties: Art Production and Kinship Patterns in the Early Modern Low Countries - Ralph Dekoninck (BMGN: Low Countries Historical Review, 2015)
Koenraad Brosens, Leen Kelchtermans, Katlijne Van der Stighelen (eds.), Family Ties: Art Production and Kinship Patterns in the Early Modern Low Countries (Turnhout: Brepols, 2012, 239 pp., ISBN 978 2 503 54227 0).